The Effect of Parents' Education Level on Children's Personality in Kanandede Village, Limbong District, North Luwu Regency - Erniah Azis (Jurnal Konsepsi, 2020)
This research is a study that discusses the influence of parents' education level on children's personality in Kanandede village, Kec. Limbong Kab. North Luwu, the level of education of parents also determines the success of their children in school. Because through education owned by parents, so parents are able to foster and educate their children at home. Even parents can direct their children based on the talents and interests of the child concerned. Thus, the level of parental education referred to in this presentation is the level of formal education that has been passed by parents from elementary school to university level. From this level, there will be differences in the level of the parents concerned. So the embodiment of the level of religious behavior is kaffah or comprehensively determined by the overall experience based on personal. The importance of parental education individually because it determines whether parents are able to foster and educate the personality of their children, so that later children can become obedient and obedient and polite to their parents. Individuals and groups sometimes have symptoms that are more troubling, namely the occurrence of several social diseases in society that are carried out by children fairly and motivations that tend to bear fruit from the failure of parents in educating their children, which has now penetrated into children who are still underage. , these violations indicate how low the religious behavior of children is so that various religious violations are trampled on, as a result, they have an impact on the social environment with the emergence of separatist actions, deprivation of the rights of others, and others. This condition of behavior is a very worrying degradation and requires a rehabilitation that requires the involvement of all parties, both parents, government, community, as well as government institutions, educational institutions and non-government institutions. This is intended to provide prevention or countermeasures so that negative behavior can be minimized so that they become Islamic, civilized and cultured children and have noble behavior.